Effectiveness and Safety of Autologous Fat Grafting to the Soft Palate Alone. (June 2015) - Boneti, Cristiano; Ray, Peter D.; Macklem, Elizabeth B.; Kohanzadeh, Som; de la Torre, Jorge; Grant, John H.
Abstract : Background: Posterior pharyngeal augmentation is an accepted method of treating velopharyngeal insufficiency (VPI). Techniques using autologous fat harvest, preparation, and grafting are well described. Based on the complications from retropharyngeal injection, we performed augmentation of the nasal surface of the palate to reduce hypernasality with decreased risks. Methods: After Institutional Review Board approval, a chart review from 2010 to 2013 identified 46 patients with cleft palate, subjective and nasoendoscopic evidence of VPI treated with autologous fat grafting to the soft palate. Speech evaluation of velopharyngeal function was compared before and after autologous fat grafting. Results: A total of 61 autologous fat grafting procedures were performed in 46 patients. The average age of the study population is 5.59 ± 2.05 years. The majority underwent a single procedure (32/46 or 69.6%), 13 of 46 patients (28.2%) had 2 fat grafting procedures and only 1 patient (2.2%) had 3 fat grafting procedures. The fat was injected primarily in the soft palate. The recorded volume of fat grafted averaged 2.4 ± 1.1 mL. Average operative time was 39 ± 12.55 minutes. There were no local or donor site complications. Four patients were lost to follow-up. Of 34 patients with adequate speech follow-up, including Pittsburgh Weighted Speech Scale (PWSS) assessment, the average preoperative score of 8.17 ± 3.59 was reduced to 5.17 ± 3.14 postoperatively. Although 26 of 34 patients (76.5%) had an improvement in their PWSS score, only 13 of 34 patients (38.23%) saw an improvement in their PWSS category. Conclusions: Autologous fat grafting to the soft palate is a safe operation with minimal risks. Speech outcomes are subjectively enhanced in the majority of patients, with a full PWSS category improvement seen in 40% of the cases. Patient selection criteria to optimize results are provided.